2006
DOI: 10.1155/ijp/2006/47917
|View full text |Cite
|
Sign up to set email alerts
|

Photo‐induced reduction of Noble metal ions to metal nanoparticles on tubular J‐aggregates

Abstract: Palladium and silver nanoparticles are formed on the surface of tubular J-aggregates of an amphiphilic tetrachlorobenzimidacarbocyanine dye by reduction of the respective metal cations in aqueous solution. Upon addition of the palladium complex Na 2 PdCl 4 to the aggregate solution, the absorption spectrum shows significant changes which is explained by partial destruction of the aggregates. Cryogenic transmission electron microscopy (cryo-TEM) images show that the tubular J-aggregates are randomly covered by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 32 publications
1
20
0
Order By: Relevance
“…Since in these experiments no electron donating molecules are present, some dyes at the aggregate surface must be oxidized. More details about this particle growth are found in a separate contribution by Kirstein et al in [99].…”
Section: Exciton Dynamics Superquenching and Electron Transfer Reacmentioning
confidence: 87%
See 1 more Smart Citation
“…Since in these experiments no electron donating molecules are present, some dyes at the aggregate surface must be oxidized. More details about this particle growth are found in a separate contribution by Kirstein et al in [99].…”
Section: Exciton Dynamics Superquenching and Electron Transfer Reacmentioning
confidence: 87%
“…Although the details of this quenching mechanism are not understood yet, this superquenching is a clear indication of efficient energy migration in the tubular J-aggregates. More experiments on fluorescence quenching are described by the contribution of Kirstein et al in [99].…”
Section: Exciton Dynamics Superquenching and Electron Transfer Reacmentioning
confidence: 99%
“…Exciton delocalization lengths of > 10 molecules as seen for cyanines are most likely not reached here. [63,64] As has been recently shown by Werz's group, chemical fixation of BODIPY units to oligomers can strongly drive J aggregate formation. [65] These authors have also observed that subtle structural modifications can have a pronounced impact on the nature of the aggregates formed.…”
Section: Class (Ii): Bodipys Prone To Aggregationmentioning
confidence: 91%
“…The degree of decoherence is traced back to information gained on the excitation location through the monitoring, turning the setup into an experimentally accessible model system for studying the effects of quantum measurements on the dynamics of a many-body quantum system. Introduction: Excitation transport through dipole-dipole interactions [1,2] plays a prominent role in diverse physical settings, including photosynthesis [3,4], exciton transport through quantum-dot arrays [5], and molecular aggregates [6][7][8]. Of crucial importance is the competition between the fundamentally coherent transport mechanism and the coupling to the environment, which has been under intense scrutiny in the context of photosynthesis (e.g.…”
mentioning
confidence: 99%